Lung cancer staging now and in the future. Issue 4 (14th February 2015) - Liam, Chong‐Kin; Andarini, Sita; Lee, Pyng; Ho, James Chung‐Man; Chau, Ngo Quy; Tscheikuna, Jamsak
Abstract For a long time lung cancer was associated with a fatalistic approach by healthcare professionals. In recent years, advances in imaging, improved diagnostic techniques and more effective treatment modalities are reasons for optimism. Accurate lung cancer staging is vitally important because treatment options and prognosis differ significantly by stage. The staging algorithm should include a contrast computed tomography (CT) of the chest and the upper abdomen including adrenals, positron emission tomography/CT for staging the mediastinum and to rule out extrathoracic metastasis in patients considered for surgical resection, endosonography‐guided needle sampling procedure replacing mediastinoscopy for near complete mediastinal staging, and brain imaging as clinically indicated. Applicability of evidence‐based guidelines for staging of lung cancer depends on the available expertise and level of resources and is directly impacted by financial issues. Considering the diversity of healthcare infrastructure and economic performance of Asian countries, optimal and cost‐effective use of staging methods appropriate to the available resources is prudent. The pulmonologist plays a central role in the multidisciplinary approach to lung cancer diagnosis, staging and management. Regional respiratory societies such as the Asian Pacific Society of Respirology should work with national respiratory societies to strive for uniform standards of care. For developing countries, a minimum set of care standards should be formulated. Cost‐effective delivery of optimal care for lung cancer patients, including staging within the various healthcare systems, should be encouraged and most importantly, tobacco control implementation should receive an absolute priority status in all countries in Asia.